Local Wisdom-Based School Literacy Movement and Elementary Students' Critical Reading Skills - Lailiya, Nirmala Rahmatul; Sukartiningsih, Wahyu; Hendratno, Hendratno (Journal of Innovation and Research in Primary Education, 2025)
This study analyzes the effectiveness of integrating local wisdom "Remo Boletan Dance" into the School Literacy Movement (GLS) on fourth-grade students' critical reading abilities at SDN Cukir 1 Jombang. A qualitative descriptive approach was employed, with data collected through participatory observations, semi-structured interviews with principals, teachers, and twelve fourth-grade students, and document analysis. Data were analyzed using thematic analysis supported by ATLAS.ti 25 software to visualize relationships between literacy movement implementation, local wisdom integration, and critical reading development. Results indicate that SDN Cukir 1 has established systematic literacy practices including daily 15-minute reading sessions and monthly "Literacy Friday" events. Integration of Remo Boletan Dance narratives into Indonesian language instruction successfully transformed students from superficial readers to critical analysts capable of questioning, evaluating, and interpreting texts within cultural contexts. Network analysis revealed strong interconnections between School Literacy Movement and local wisdom themes, demonstrating synergistic effects on both literacy competencies and cultural identity formation. Supporting factors included comprehensive stakeholder engagement from administrators, teachers, parents, and community organizations, while challenges involved reading fluency gaps and variable student motivation. This study contributes empirical evidence that culturally responsive literacy instruction through local wisdom integration effectively enhances critical reading skills while preserving cultural heritage, offering a replicable framework for elementary schools implementing contextually relevant literacy programs.